1993
DOI: 10.1093/glycob/3.2.131
|View full text |Cite
|
Sign up to set email alerts
|

The vascular E-selectin binds to the leukocyte integrins CD11/CD18

Abstract: Leukocyte adhesion involves at least three molecular families of adhesion proteins: the leukocyte integrins CD11/CD18, the intercellular adhesion molecules (ICAMs) and the carbohydrate-binding L-, E- and P-selectins. The intercellular adhesion molecules are well-known ligands for the CD11/CD18 integrins. We now show that E-selectin specifically binds to the sialyl Lex carbohydrate epitopes of leukocyte integrins. Thus, the different families of leukocyte adhesion molecules form an integrated adhesion network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…[34][35][36] However, mouse L-selectin has been shown not to bind mouse E-selectin, making this an unlikely ligand in our study. 35 E-selectin ligand-1 (ESL-1), 37,38 CD66-nonspecific cross-reacting antigen, 39 CD43, 40 and ␤ 2 integrin 41,42 have all been proposed as potential ligands on leukocytes for E-selectin, although CD43 does not appear to support rolling and to our knowledge ␤ 2 integrin and CD66 are not down-regulated. Recently, a family of glycolipids, namely ␣2,3-sLe x glycosphingolipids, have also been shown to support E-selectin-dependent rolling.…”
Section: Discussionmentioning
confidence: 89%
“…[34][35][36] However, mouse L-selectin has been shown not to bind mouse E-selectin, making this an unlikely ligand in our study. 35 E-selectin ligand-1 (ESL-1), 37,38 CD66-nonspecific cross-reacting antigen, 39 CD43, 40 and ␤ 2 integrin 41,42 have all been proposed as potential ligands on leukocytes for E-selectin, although CD43 does not appear to support rolling and to our knowledge ␤ 2 integrin and CD66 are not down-regulated. Recently, a family of glycolipids, namely ␣2,3-sLe x glycosphingolipids, have also been shown to support E-selectin-dependent rolling.…”
Section: Discussionmentioning
confidence: 89%
“…The soluble E-selectin and VCAM-1 were produced by deletion of the transmembrane and cytoplasmatic domains of full-length protein. The proteins were expressed from the pGW 1 HG vector in Chinese hamster ovary cells and purified on mAb affinity columns, as described (33). The purified protein was detected by a specific ELISA (British Biotechnology Products) and shown to be biologically active in cell binding assays (32).…”
Section: Methodsmentioning
confidence: 99%
“…A molecule known as E-selectin ligand-1 (ESL-1) serves as an E-selectin ligand on mouse neutrophils (7), but it is not expressed on human neutrophils nor on human hematopoietic stem and progenitor cells (HSPCs) (8). Biochemical assays have indicated that the leukocyte β 2 integrins LFA-1 (lymphocyte function-associated antigen 1 or CD11a/ CD18) and MAC-1 (macrophage-1 antigen or CD11b/CD18) can serve as E-selectin ligands on human leukocytes (9). CD43 has also been implicated to be an E-selectin ligand on mouse neutrophils and activated T cells (10), and we have reported that CD43 on human T cells can bind E-selectin, but not P-selectin (11).…”
mentioning
confidence: 99%